PENYELESAIAN SENGKETA TANAH TERHADAP SERTIFIKAT GANDA MELALUI MEDIASI DI BADAN PERTANAHAN NASIONAL KABUPATEN KUBU RAYA - NIM. A1012191142, IRNA ANGGRAENI WAHDANIAH (Fakultas Hukum Universitas Tanjungpura, 2025)
AbstractArticle 27 of Government Regulation No. 24 of 1997 on Land Registration has been amended by Government Regulation No. 18 of 2021 concerning Management Rights, Land Rights, Condominium Units, and Land Registration, along with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (Permen ATR/BPN) No. 14 of 2024. These regulations provide an option for resolving land disputes through mediation between parties. The National Land Agency (Badan Pertanahan Nasional) plays a key role as a mediator, focusing on consensus-based decisions grounded in a win-win solution approach. However, a critical issue arises regarding whether mediation decisions can ensure legal certainty for landowners with overlapping certificates and guarantee the implementation of such decisions, particularly in disputes occurring in Kuburaya Regency. The research problem addressed in this study is: